Interaction of Transition-Metal-Substituted Heteropolytungstates with Adenosine and Determination of the Site Coordination - Ahmdabadi, Zahra; Reissi, Heidar; Faramarz Tayyari, Sayyed (Asian Journal of Chemistry, 2010)
The complexes of Keggin and Dawson structures of transition-metal-substituted heteropolytungstates (Cs5[PW11O39M-OH2]·xH2O and K8[P2W17O61M-OH2]·yH2O where M is Mn2+, Co2+, Ni2+ and Zn2+) with adenosine have been synthesized and characterized. The UV-visible Fourier transform IR; 1H-NMR spectra show an interaction between transition-metal- substituted heteropolytungstates and adenosine. Our spectroscopic data show transition-metal-substituted heteropolytungstates coordinated with adenosine molecule through N(7) of imidazole ring and have a direct interaction in solid phase. It seems the interaction of Cs5[PW11O39M-OH2]·x H2O with adenosine is indirect in solution.